Relationship Between Gross Motor Skills and Inhibitory Control in Preschool Children: A Pilot Study - Liu, Jiajia; Li, Yiyan; Zhou, Tang; Lu, Yanhua; Sang, Menghao; Li, Longkai; Fang, Chunyi; Hu, Wenwen; Sun, Xiaojiao; Quan, Minghui; Liu, Jinyan (Frontiers in Human Neuroscience, 2022)
Purpose Gross motor skills (GMS) and inhibitory control (IC) which are both development in preschool stage is significant for preschooler to healthy growth. However, the evidence of relationship between them in preschoolers are still insufficient, most of studies only focus on youth. Thus, the aim of this research is to examine the association between GMS and IC in preschool children. Methods This cross-sectional study used baseline data from a previous intervention study of preschoolers conducted in 2018. GMS were assessed by using the Test for Gross Motor Development (2nd edition) in preschoolers, which includes two subtests of locomotor and object control skills. Total GMS is calculated from the sum of these two subtests. The Fish Flanker task was used to evaluate both accuracy and reaction time of IC. Multivariate linear regression models were established to analyze the relationships between GMS and IC. Results A total of 123 preschool-age children (55 girls, 68 boys) were included in the final analysis. After adjusting for confounders, GMS (β = −8.27 ms, 95%CI: −14.2, −2.34), locomotor (β = −11.2 ms, 95%CI: −21.43, −0.97), and object control skills (β = −12.15 ms, 95%CI: −22.07, −2.23) were all negatively related with reaction time of IC. Conclusion There was a significant negative correlation between gross motor skills and the reaction time of inhibitory control in preschool children. Further research is needed to verify this finding in prospective and experimental studies.